Teacher’s perceptions and practices of using Phonics software to teach English at a primary school in Hanoi = Nhận thức và thực tiễn của giáo viên về việc sử dụng phần mềm Phonics để dạy tiếng Anh tại một trường tiểu học ở Hà Nội. M.A. Thesis. - Nguyễn, Quỳnh Hoa (2019)
The study examined teachers‟ perceptions of using of Phonics software and their practices in classroom at a primary school in Soc Son district. Three teachers were invited to join this research. The study was carried out with two data collection techniques: interview and observation.The findings indicated that teachers had both positive and negative perceptions towards the use of Phonics software.